577 Infra-Inguinal Bypass Graft Surveillance Is an Opportunity to Optimise Statin and Antiplatelet Therapy to Reduce 12-Month Major Amputation and Mortality Rates. (19th August 2022) - Laloo, Ryan; Gadsby, Georgia; Jauniaux, Benoit; Bailey, Marc; Scott, Julian
Abstract: Aim: Infra-inguinal bypass graft failure within the first two postoperative years can result from stenotic lesions within the conduit and near anastomosis. This study assesses graft surveillance uptake, patency, amputation, and death rates among infra-inguinal bypass surgery patients at 1, 6 and 12-months postoperatively. Method: Patients undergoing infra-inguinal bypass at a single vascular centre between 1 st January 2018 and 31 st December 2019 were identified from the prospectively collected database. Primary outcomes at 1, 6 and 12-months postoperatively included: duplex-ultrasound (DUS) surveillance uptake, patency, major amputations, and death rates. Statistical analysis with SPSS® was performed using chi-squared tests and paired sample t-tests. Results: Of the 91 patients included, 79.1% were men and median(IQR) age was 71(62–76). At 1, 6 and 12 months, DUS uptake was 74.2%, 77.5% and 73.3% respectively, primary-assisted patency rates were 88.2%, 78.8% and 65.3% respectively and secondary patency rates were 97.6%, 96.3% and 96.3% respectively. Major amputation rates at 1, 6 and 12 months were 5.4%, 8.6%, 8.6% respectively. Death rates at 1, 6 and 12 months were 3.2%, 5.4% and 10.8% respectively. Patients on statin therapy post-operatively had lower 12-month mortality than those not on statin therapy (7.7% vs 30.0%, p=.028). Major amputation rate at 12 months was lower among patients prescribed antiplatelet therapy (6.3% vs 40%, p=.008). Conclusions: DUS graft surveillance is a vital opportunity to adequately optimise statin and antiplatelet therapy post-revascularisation to reduce 12-month major amputation and mortality rates.